Serum Albumin Levels and Clinical Outcomes Among Ischemic Stroke Patients Treated with Endovascular Thrombectomy - Gao J (Dove Medical Press, 2021)
Jie Gao,1,* Ying Zhao,1,* Mingyang Du,2,* Hongquan Guo,3 Ting Wan,1 Min Wu,3 Ling Liu,1 Huaiming Wang,1,4 Qin Yin,1 Xinfeng Liu1 1Department of Neurology, Jinling Hospital, Medical School of Nanjing University, Nanjing, Jiangsu, 210000, People’s Republic of China; 2Cerebrovascular Disease Treatment Center, Nanjing Brain Hospital Affiliated to Nanjing Medical University, Nanjing, Jiangsu, 210000, People’s Republic of China; 3Department of Neurology, Jinling Hospital, Southern Medical University, Nanjing, 210000, People’s Republic of China; 4Department of Neurology, The 80th Group Army Hospital, Weifang, Shandong, 261000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huaiming WangDepartment of Neurology, Jinling Hospital, Medical School of Nanjing University, No. 305 East Zhongshan Road, Nanjing, 210002, Jiangsu Province, People’s Republic of ChinaTel +86 2584801861Fax +86 2584805169Email wanghm89@163.comQin YinDepartment of Neurology, Jinling Hospital, Medical School of Nanjing University, No. 305 East Zhongshan Road, Nanjing, 210002, Jiangsu Province, People’s Republic of ChinaTel +86 2584801861Fax +86 2584805169Email yinqin9912@163.comBackground and Aims: Albumin levels have been reported to be associated with all-cause and cardiovascular mortality. The aim of this study was to investigate the association between serum albumin and prognosis of ischemic stroke patients after endovascular thrombectomy (EVT) treatment.Methods: Patients with EVT due to large artery occlusion in anterior circulation were selected from ACTUAL (endovascular treatment for acute anterior circulation) ischemic stroke multicenter registry in China. Serum albumin levels were measured within 24 h of admission. The primary outcome was poor functional outcome (modified Rankin scale score of 3– 6) at three months. Secondary outcomes were symptomatic intracranial hemorrhage (sICH) and three-month mortality.Results: A total of 605 patients (mean age, 64.2 years; 59.3% male) were enrolled. Up to three months after stroke, 342 patients (56.5%) developed poor functional outcome. After multivariate adjustment for demographic characteristics, National Institutes of Health stroke score, and other potential confounders, the odds ratio for the lowest tertile of serum albumin levels was 2.43 (95%CI, 1.18− 5.01; P=0.046) for poor functional outcome, compared with the highest category. Restricted cubic spline regression demonstrated a linear association between albumin levels and poor functional outcome (P for linearity=0.017). Subgroup analyses further confirmed these results. Similar significant findings were also found in the association of serum albumin with mortality, but not with sICH.Conclusion: Decreased serum albumin levels were independently associated with poor prognosis at 90 days after acute large vessel occlusion stroke in anterior circulation treated with EVT.Keywords: albumin, ischemic stroke, endovascular treatment, prognosis